Effect of long-term exposure to air pollution on anxiety and depression in adults: A cross-sectional study - Vert, Cristina; Sánchez-Benavides, Gonzalo; Martínez, David; Gotsens, Xavier; Gramunt, Nina; Cirach, Marta; Molinuevo, José Luis; Sunyer, Jordi; Nieuwenhuijsen, Mark J.; Crous-Bou, Marta; Gascon, Mireia (International journal of hygiene and environmental health, 2017)
The association between exposure to air pollutants and mental disorders among adults has been suggested, although results are not consistent. To analyze the association between long-term exposure to air pollution and history of anxiety and depression disorders and of medication use (benzodiazepines and antidepressants) in adults living in Barcelona. A total of 958 adults (45–74 years old) residents in Barcelona, most of them having at least one of their parents diagnosed with dementia (86%), and participating in the ALFA (Alzheimer and Families) study, were included. We used Land Use Regression (LUR) models to estimate long-term residential exposure (period 2009–2014) to PM2.5, PM2.5 absorbance (PM2.5 abs), PM10, PM coarse, NO2 and NOx. Between 2013 and 2014 participants self-reported their history of anxiety and depression disorders and related medication use. The analysis was focused on those participants reporting outcome occurrence from 2009 onwards (until 2014). We observed an increased odds of history of depression disorders with increasing concentrations of all air pollutants [e.g. an increased odds of depression of 2.00 (95% CI; 1.37, 2.93) for each 10μg/m3 NO2 increase]. Such associations were consistent with an increased odds of medication use in relation to higher concentrations of air pollutants [e.g. an increased odds of antidepressants use of 1.23 (1.04, 1.44) for each 20μg/m3 NOx increase]. Associations regarding anxiety disorders did not reach statistical significance. Our study shows that increasing long-term exposure to air pollution may increase the odds of depression and the use of antidepressants and benzodiazepines. Further studies are needed to replicate our results and confirm this association.